The Effect of Problem-Based Learning Models Through Map Media on Spatial Intelligence and Problem Solving Skills - Marzuqi, Muhammad Ilyas (Universitas Negeri Surabaya, 2019)
This research was based on the existence about the important of spatial Intelligences as based for problem solving skills. The purpose of the study was to know the increase of spatial intelligence and problem-solving skills of learners that are subjected to problem-based learning through the map media. And to know how big the correlation between spatial intelligence and problem solving skills. The design of this study was Quasi Experimental or quasi-experimental design in the form of Nonequivalent Control group pre test post test design. The hypothesis was tested by using statistical parametric independent sample t test and non-parametric Mann Whitney, followed by n-gain test score as well as the calculation of correlation and regression linearity. The results showed a significant improvement in terms of spatial intelligence between classroom space experiments using map media with grade control and the experimental class using photo media. There was a significant improvement in their to solve problems skills between the two classes of experiments using problem based learning with control classroom using expository models. Then there is a very strong correlation between spatial intelligence variables with the variable problem-solving skills, as well as a significant influence on the spatial intelligence problem-solving skills.